A comparison of career satisfaction amongst dental healthcare professionals across three health care systems: Comparison of data from the United Kingdom, New Zealand and Trinidad & Tobago - Newton J; Naidu Rahul; Ayers Katie (BMC, 2006)
Abstract Background The aim of this study was to compare the expressed levels of career satisfaction of three groups of comparable dental healthcare professionals, working in Trinidad, the United Kingdom and New Zealand. Methods Three questionnaire surveys were carried out of comparable dental healthcare professionals. Dental nurses in Trinidad and dental therapists in the UK and New Zealand. Questionnaires were sent to all registered dental nurses or dental therapists. Results Career satisfaction was lowest amongst Dental Therapists working in Trinidad and Tobago. Approximately 59% of the Therapists working in New Zealand reported stated that they felt they were not a valued member of the dental team, the corresponding proportion in the United Kingdom was 32%, and for Trinidad 39%. Conclusion Dental therapists working in different healthcare systems report different levels of satisfaction with their career.